DEVELOPMENT OF STUDENT WORKSHEET BASED ON A REALISTIC APPROACH TO IMPROVE STUDENTS' MATHEMATICAL PROBLEM-SOLVING ABILITIES AT SMP NEGERI 30 MEDAN - Nazri Maulana Khani; Endah Dwi Atika; Putri Elmaretha Purba (Yayasan Amanah Nur Aman, 2026)
This study aims to determine the improvement of students' mathematical problem-solving abilities through Student Worksheets developed with a realistic approach. This research was conducted at SMP Negeri 30 Medan. This type of research is development research. The development carried out is the development of learning tools that refer to the 4-D development model (four-D Model) proposed by Thiagarajan, Semmel and Semmel. This model includes four stages: Define, Design, Develop, and Disseminate. Due to the limitations of the researchers, the research was conducted up to the development stage. The subjects of this study were students in grades VII-6 and VII-8 of SMP Negeri 30 Medan. The instruments used to measure the quality of the developed STUDENT WORKSHEET were the RPP and STUDENT WORKSHEET assessment sheets to measure validity, and a test of students' mathematical problem-solving abilities. The results of the study showed that the classical learning completeness had exceeded the minimum limit of 94% in trial 2. The achievement of indicators/completeness of learning objectives had been achieved for each indicator in trial 2. Students' mathematical problem-solving abilities had increased with the number of students who completed trial 1 only 59% increasing by 35% to 94% in trial 2. The average class value also increased from trial 1 of 67.08 to 83.66 in trial 2. So it can be concluded that the development of STUDENT WORKSHEET based on a realistic approach can improve students' mathematical problem-solving abilities